FEATURES OF THE BIOECONOMIC TRANSFORMATION OF EU INDUSTRY SECTORS - VOSTRIAKOVA, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The need for bio-economic transformation of industries has appeared on the agenda in response to the need to find alternatives to fossil resources. This idea is based on the increased use of biotechnology and biofuels and is a response to the growing concern about the irrational use and management of limited natural resources. The relevance of the study lies in the need to study the experience of European countries on the way to the bio-economic transformation of industries and determine its features for the further formation of appropriate strategies and policies in Ukraine on the way to joining the European Union and post-war economic recovery. The article examines modern concepts and paradigms of bio-economy development in the countries of the European Union. On the basis of the conducted theoretical research of literary sources and program documents, the key characteristics of the bio-economic transformation of the national economy were formed. An assessment of the real contribution of the bio-economy to the national economy of the European Union by economic sector and its dynamics was made. It was established that the share of the bio-economy of the European Union during the last five years has not been significant, but stable growth. Despite the fact that the largest share in the bio-economic sector of the union is occupied by agricultural production and the food industry, gradual shifts are also taking place in other industries that are not purely biological. In order to develop a theoretical and methodological basis for the classification of bio-economy sectors, taking into account their specification and features, we have developed a model of three-dimensional classification of of bio-economic transformation branches, which includes the "bio-resource", "transformational" and "bio-innovative" distribution of industries. Such a division will make it possible to develop appropriate strategies and policies for the bio-economic transformation of Ukraine’s industries, taking into account their historical and sector characteristics, as well as the specificity of perception in the sector.